Internship at public school: Institución Educativa Antonia Santos, teaching vocabulary to preschoolers through the project approach (2022)
In Colombia, the teaching of English is promoted compulsorily from primary to secondary education, while in preschool, it is suggested. As a consequence, there is a gap in the teaching-learning of the second language from the beginning of schooling. Nonetheless, early childhood education offers students a comprehensive environment where the dimensions of development, soft skills, and competencies such as language acquisition and interpersonal skills are encouraged. Therefore, this report describes my experience during my internship as a preschool English teacher at the Antonia Santos school in Montería, Córdoba. To accomplish this, I applied The Project Approach to extend vocabulary in preschool students. In addition, this document illustrates the findings and achievements related to my students' growth, personal improvements, and professional advancement.